Chemical, Electrochemical and Computational Studies of Newly Synthesized Novel and Environmental Friendly Heterocyclic Compounds as Corrosion Inhibitors for Mild Steel in Acidic Medium - Mishra A.; Verma C.; Srivastava V.; Lgaz H.; Quraishi M.A.; Ebenso E.E.; Chung I.-M. (My University, 2025)
The present study describes the microwave-induced aqueous phase synthesis, characterization, and corrosion inhibition effect of five heterocyclics containing nitrogen, oxygen, and sulfur (designated by CINH-1 to CINH-5) for mild steel in 1 M HCl. The effectiveness of the newly synthesized heterocyclics has been evaluated using experimental and theoretical methods. Weight loss study revealed an increased effectiveness of the CINH molecules with increase in their concentrations and acquired the highest values of 82.38, 85.79, 88.93, 92.61, and 95.45% for CINH-1, CINH-2, CINH-3, CINH-4, and CINH-5, respectively, at 39.8 × 10−5 M concentration. Polarization study revealed that studied CINH molecules as cathodic-type inhibitors. EIS study showed that CINH molecules behave as interface type of corrosion inhibitors and enhance polarization resistances in their presence. Their adsorption at the interfaces obeyed the Temkin adsorption isotherm. The inhibition effect of the investigated CINH molecules was further supported by surface morphological studies using atomic force microscopy and scanning electron microscopy methods. Several DFT parameters such as ∆E, χ, η, σ, µ, and ∆N based on the values of frontier molecular energies (EHOMO and ELUMO) have been evaluated and employed to describe the inhibition action of the tested CINH molecules. Using MD simulations, orientation of the CINH molecules and adsorption energies for their interactions with metallic surface have been determined. Experimental and theoretical consequences were in good agreement. © 2018, Springer International Publishing AG, part of Springer Nature.